The expression of hypoxia-inducible factor-1 in primary brain tumors. (1st September 2013) - Reszec, Joanna; Rutkowski, Robert; Chyczewski, Lech
<x xml:space="preserve">Abstract</x> Purpose: Primary brain tumors are common type of neoplasms. The most common are astrocytic tumors, so do meningiomas of various grades. The etiology is still unknown; however, there are lots of data presenting new theories about genetic alterations responsible for low- or high-grade astrocytic tumors development as well as meningiomas, despite this the results are divergent. The aim of the study was to evaluate hypoxia-inducible factor-1 (HIF-1) expression in meningiomas and astrocytic tumors of various grades. Material and methods: One hundred six cases of astrocytic tumors were divided into diffused astrocytoma (24 cases), anaplastic astrocytoma (40 cases) and glioblastoma groups (42 cases). Among glioblastoma group, 30 cases were secondary glioblastoma. One hundred fifty-four meningioma cases were divided as low-grade meningioma (G1: 104 cases) and high-grade meningioma groups (G2: 43 cases and G3: 7 cases). Twelve low-grade meningiomas transformed into high-grade tumors, 17 low-grade meningiomas recur within 12 years. HIF-1 expression was estimated using immunohistochemistry under the light microscope. Statistical analysis was performed in all examined groups. Results: HIF-1 expression was observed in 37.5% cases of diffused astrocytomas, in anaplastic astrocytomas 27.5% tumors were HIF-1 positive, in the glioblastoma goup HIF-1 expression was observed in 83.3% cases. All secondary glioblastomas were positive for HIF-1. Low-grade meningiomas were positive for HIF-1 in 55.7%, in high-grade meningiomas, HIF-1 expression was observed in 84%. All meningiomas, which progressed from low- to high-grade meningiomas, were HIF-1 positive. Conclusion: HIF-1 expression is associated with the development and progression of both astrocytic tumors and meningiomas.